First round Dataset: Impacts of Improved Bean Technology on Smallholder Productivity and Food Security in Burundi - Katungi, Enid Mbabazi; Nduwarugira, Eric; Ntukamazina, Jean Nepomuscene; Niragira Sanctus; Mutua, Mercy Muli; Kalemera, Sylvia Monica; Nchanji, Eileen; Birachi Eliud; Rubyogo, Jean Claude (2025)
In July-August 2019, CIAT-PABRA and ISABU collected household-level data in Burundi to evaluate a bean research project funded by SDC and Global Affairs Canada. This first impact assessment for the project analyzed the adoption of improved bean varieties and their effects on yields and food security, using farmer recall. For variety identification, the study combined farmer recall with DNA fingerprinting. However, the initial impact analysis in 2020 was based on farmer recall, as the DNA results were not available at the time of publication. This is data collected in round one. Methodology:The data were collected by researchers who have good knowledge in French and kirundi and have extensive experience in bean production context of Burundi. The team trained for 5 days in the questions written in English. Prior to the actual survey, the questionnaires were translated from English into French, uploaded onto tablets and pretested on few selected farmers. A community questionnaire was administered to key informants (i.e. village leaders and elders) during the first round of the survey and gathered information on the village level variables including the institutional aspects, such as access to information, seed, seed distribution programs, credit, roads, and market infrastructure and cultivar changes, and agro-climatic shocks.